2017
DOI: 10.1371/journal.pone.0173573
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetaminophen on ubiquitin homeostasis in Saccharomyces cerevisiae

Abstract: Acetaminophen (APAP), although considered a safe drug, is one of the major causes of acute liver failure by overdose, and therapeutic chronic use can cause serious health problems. Although the reactive APAP metabolite N-acetyl-p-benzoquinoneimine (NAPQI) is clearly linked to liver toxicity, toxicity of APAP is also found without drug metabolism of APAP to NAPQI. To get more insight into mechanisms of APAP toxicity, a genome-wide screen in Saccharomyces cerevisiae for APAP-resistant deletion strains was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In our previous research (Huseinovic et al 2017a , b ), we showed that APAP toxicity depends on cellular ubiquitin levels and that ubiquitin-deficient strains, such as ubi4∆ , doa1∆, doa4∆ , ubp6∆ and ∆ubp14, conferred resistance to APAP (Huseinovic et al 2017b ). Since it is known that the Tat2 expression level is stabilized in deletion strains doa4∆ , ubp6∆ and ubp14∆ under high pressure (Miura and Abe 2004 ), and based on our current finding that only Tat1 or Tat2 overexpression conferred resistance to APAP, we hypothesized that the Tat2 expression level is stabilized in the APAP resistant mutants during APAP treatment.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In our previous research (Huseinovic et al 2017a , b ), we showed that APAP toxicity depends on cellular ubiquitin levels and that ubiquitin-deficient strains, such as ubi4∆ , doa1∆, doa4∆ , ubp6∆ and ∆ubp14, conferred resistance to APAP (Huseinovic et al 2017b ). Since it is known that the Tat2 expression level is stabilized in deletion strains doa4∆ , ubp6∆ and ubp14∆ under high pressure (Miura and Abe 2004 ), and based on our current finding that only Tat1 or Tat2 overexpression conferred resistance to APAP, we hypothesized that the Tat2 expression level is stabilized in the APAP resistant mutants during APAP treatment.…”
Section: Resultsmentioning
confidence: 89%
“…Previously, we used yeast Saccharomyces cerevisiae as a eukaryotic model organism to get more insight into NAPQI independent APAP toxicity, because yeast lacks the genes coding for drug-metabolizing P450 enzymes and is incapable of APAP metabolism and formation of NAPQI (Srikanth et al 2005 ). Our study revealed that APAP toxicity depends on the cellular concentration of ubiquitin: ubiquitin depletion confers resistance to APAP, whereas ubiquitin overexpression caused sensitivity (Huseinovic et al 2017b ). Based on the correlation between ubiquitin levels and APAP-induced toxicity, we also performed a deubiquitinase (DUB) gene deletion screen (Huseinovic et al 2017a ).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…With its analgesic and antifever properties, and its low risk at the recommended dose, acetaminophen is widely used as an over-the-counter drug [ 1 ]. Acetaminophen poisoning is one of the significant causes of liver damage, and the use of this drug in chronic form may cause serious health problems [ 2 , 3 ]. Acetaminophen is converted to non-toxic metabolites in phase II metabolism.…”
Section: Introductionmentioning
confidence: 99%